2012
DOI: 10.1371/journal.pone.0044376
|View full text |Cite
|
Sign up to set email alerts
|

Coevolution in RNA Molecules Driven by Selective Constraints: Evidence from 5S rRNA

Abstract: Understanding intra-molecular coevolution helps to elucidate various structural and functional constraints acting on molecules and might have practical applications in predicting molecular structure and interactions. In this study, we used 5S rRNA as a template to investigate how selective constraints have shaped the RNA evolution. We have observed the nonrandom occurrence of paired differences along the phylogenetic trees, the high rate of compensatory evolution, and the high TIR scores (the ratio of the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 58 publications
(66 reference statements)
0
12
0
Order By: Relevance
“…We conclude with thoughts about the future of the field. Although we focus on proteins, the concepts and techniques we discuss can also be applied to DNA and RNA evolution 38-41 . We highlight experimental work, but computational and theoretical explorations have also contributed to the development of the new field 42,43 .…”
mentioning
confidence: 99%
“…We conclude with thoughts about the future of the field. Although we focus on proteins, the concepts and techniques we discuss can also be applied to DNA and RNA evolution 38-41 . We highlight experimental work, but computational and theoretical explorations have also contributed to the development of the new field 42,43 .…”
mentioning
confidence: 99%
“…Specifically, although biologically functional secondary-structural elements should be evolutionarily conserved across diverse viral lineages, the nucleotide sequences from which these elements are composed should display distinctive signals of natural selection favoring the maintenance of these structures. Whereas in coding regions these signals might include codon usage biases (54,55) and decreased rates of synonymous substitution (56), throughout the genome these signals could also include high rates of reversion substitution (51,57) and increased frequencies of complementarily coevolving nucleotide pairs, particularly among those nucleotides predicted to be base paired within secondary-structural elements (58)(59)(60).…”
mentioning
confidence: 99%
“…Paired means that the first mutated base is paired with the second mutated base, while the unpaired means that the two mutated bases are unpaired. We calculated the ratio paired/unpaired and surprisingly found that the ratio is lower than the expected value in the two species ( t -test, all p- values <10 −7 , Table 3), which is different from the pattern inferred from the conserved secondary structure (the ratio is higher than the expected value) [27]. This result is consistent with the idea that structural stability instead of structural conformation in HSR is conserved during evolution [16], [35].…”
Section: Resultsmentioning
confidence: 47%
“…Besides the strategy involving the reduction of the substitution rate on key sites (as suggested in previous section), another strategy is used to decrease the harm of the mutations on key sites. That is, a second (so called “compensatory”) mutation occurs on the specific site to restore the original conformation [27], [50], [51]. Previous studies on conserved secondary structure have revealed that the compensatory mutations should have a fitness equivalent to the wild type, resulting in an increasing of the substitution rate among these specific sites compared with that of key sites [52].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation